Recrystallization techniques for the synthesis of ZnO nanorods: an in situ process for carbon doping and enhancing the dispersion concentration of ZnO nanorods. Issue 30 (9th May 2018) - Hossain, Muhammad Mohsin; Islam, Md. Akherul; Shima, Hossain; Hasan, Mudassir; Hilal, Muhammad; Lee, Moonyong
Abstract : Dispersed ZnO hexagonal nanorods in ethanol solvent and its interfacial behavior in this liquid phase. Abstract : Zinc acetate is recrystallized as lumber-shaped tetragonal rods by a novel recrystallization technique. Subsequently, the recrystallized zinc acetate is converted into ZnO nanorods in a glass vial by the simplest and cheapest method without utilizing any expensive instrumentation. Carbon is doped in ZnO nanorods during the preparation ZnO nanorods without any extra steps, chemicals, or effort. The carbon-doped ZnO nanorods can be dispersed in a solvent at very high concentrations and are also stable for a very long time, which are comparatively higher than those of the other existing ZnO nanoparticles. The higher dispersion concentration and higher stability of ZnO nanoparticles are explained by a scheme that demonstrates the suspending mechanism of the ZnO nanoparticles at higher concentrations with higher stabilities in a solvent through the anchoring groups of carbon. No materials are used for surface modification; no surface coatings, ionic materials, or pH controlling materials are used to increase the dispersion concentration and stability. This is the first observation of the doped carbon playing a significant role in the dispersion of ZnO nanoparticles at higher concentrations by withholding them in the solvent. Therefore, doped carbon at the surface of ZnO nanoparticles prevents the self-aggregation of ZnO nanoparticles in the solution phase by interfacial barrier layers among ZnO nanorods and interfacial interactive layer between ZnO nanorod and solvent.